Intestinal fermentation in vitro models to study food-induced gut microbiota shift: an updated review. Issue 12 (8th June 2020) - Nissen, Lorenzo; Casciano, Flavia; Gianotti, Andrea
ABSTRACT: In vitro gut fermentation models were firstly introduced in nutrition and applied microbiology research back in the 1990s. These models have improved greatly during time, mainly over the resemblance to the complexity of digestion stages, the replication of experimental conditions, the multitude of ecological parameters to assay. The state of the science is that the most competitive models shall include a complex gut microbiota, small working volumes, distinct interconnected compartments and rigorous bio-chemical and ecological settings, controlled by a computer, as well as a free-hands accessibility, not to contaminate the mock microbiota. These models are a useful tool to study the impact of a given diet compound, e.g. prebiotics, on the human gut microbiota. The principal application is to focus on the shift of the core microbial groups and selected species together with their metabolites, assaying their diversity, richness and abundance in the community over time. Besides, it is possible to study how a compound is digested, which metabolic pathways are triggered, and the type and quantity of microbial metabolites produced. Further prospective should focus on challenges with pathogens as well as on ecology of gut syndromes. In this minireview an updated presentation of the most used intestinal models is presented, basing on their concept, technical features, as well as on research applications. Abstract : Intestinal in vitro models to study changes in the composition and metabolism of the gut microbiota in response to the diet.